Challenging conventions: Charging habitual movements in domestic kitchens - Larsson, Nathanael (My University, 2022)
This study investigates the potential of kitchen topologies as a tool for stimulating physical activity. The latest recommendations for physical activity in Sweden by YFA (Yrkesföreningar för fysisk aktivitet /Swedish Professional Associations for Physical Activity) state the urgent need for increased physical activity and a lessened amount of sitting still. As a response, this investigation starts at the heart of the home, the vibrant and beating room for activity — the kitchen. Where better to induce motor practice and cognitive skills than in a domestic place intended for work involving all human senses? A century has passed since the emergence of ergonomics and our western modern kitchen. The normative visions for a good life, functionality and comfort at that time, follow us to this day, yet contemporary problems are rather different. Health issues related to a sedentary lifestyle are most common in western developed countries. Regardless of the causal relationship between ergonomics and human well-being it is significant to question how the built environment shapes human living. In general terms, how can the built environment encourage a long life of healthy habits? More particularly, this study investigates how design interventions in the kitchen can activate a contemporary sedentary lifestyle, encouraging bodily engagement, motor practice and cognitive training. Through a speculative design, this work presents perspectives on habitual movements inside the domestic kitchen. Can healthy habits be encouraged without impeding on bodily integrity? With a primary focus on actions involving fully embodied movements such as; reaching, bending and twisting, the design attempts to encourage more vibrant, diverse and physically active domestic habits. The investigated actions are posed as a dialogue with a set of design statements including low counter spaces, climbable structures and a strict removal of chairs. The design is motivated by a vision regarding physical engagement as something elegant and an integral part of habitual movement.
Keywords: Kitchen; Ergonomics; Domestic; Convention; Habits; Habitual; Movement; Physical activity